OUTCOMES OF PRIMARY PERCUTANEOUS CORONARY INTERVENTION IN PATIENTS WITH ST- ELEVATION MYOCARDIAL INFARCTION (Journal of Medical & Health Sciences Review, 2025)
Background: ST-elevation myocardial infarction (STEMI) has been one of the most common causes of morbidity and death at the population level worldwide. Primary percutaneous coronary intervention (PCI) has been declared the gold standard reperfusion strategy with the best outcomes in opposition to the alternative therapies.Objective: To compare clinical outcomes, complications, and short- term prognosis of STEMI patients who received primary PCI in a tertiary cardiac care hospital.Methods: The prospective observational study design was carried out in the Armed Forces Institute of Cardiology, Rawalpindi, from 15 December 2024 to 15 June 2025. Two hundred patients who had been treated with PCI as the primary treatment and had confirmed STEMI were included. Demographic data, angiographic data, complications, and outcomes were recorded and evaluated.Results: The successful reperfusion (TIMI-3 flow) rate was 91 percent. Mortality rate in the hospital was 2.5 percent, and the cumulative 30-day mortality rate was 6.5 percent. The complicated factors were arrhythmias (14 percent), cardiogenic shock (9 percent), and no-reflow (6 percent). Major adverse cardiovascular events occurred in 11%.Conclusion: Primary PCI is the best reperfusion strategy, with acceptable complication rates, and this fact not changed, as it is the foundation of STEMI management.